Learning to Teach Graduate Students: A Self-Study by Students and a Faculty Member. (February 2016) - Conway, Colleen; Palmer, C. Michael; Edgar, Scott; Hansen, Erin
This study examined our perceptions as a music education professor and three PhD students as we conducted a self-study of our individual and collective experiences teaching graduate students. We framed our work around the key question: How do PhD students describe experiences specifically in relation to perceived potential as teachers of graduate students in higher education? Findings concerning graduate teaching included (a) views of graduate teaching changed with increased experience, and (b) confidence increased with more experience teaching graduate classes and more time to process the content. The use of self-study as an approach to inquiry is discussed along with these findings.